Aid, Exports, and Growth : A Time-Series Perspective on the Dutch Disease Hypothesis - Kang, Joong (IMF Working Papers; Working Paper ;, 2013)
We use a heterogeneous panel VAR model identified through factor analysis to study the dynamic response of exports, imports, and per capita GDP growth to a 'global' aid shock. We find that a global aid shock can affect exports, imports, and growth either positively or negatively. As a result, the relation between aid and growth is mixed, consistent with the ambiguous results in the existing literature. For most countries in the sample, when aid reduces exports and imports, it also reduces growth; and, when aid increases exports and imports, it also increases growth. This evidence is consistent with a DD hypothesis, but also shows that aid-receiving countries are not 'doomed' to catch DD.